Effect of Hand and Foot Massage Toward Pain Level in Postpartum Mother with Sectio Caesarea: Case Report - Salamah, Umi; Astuti, Yuni (Universitas Muhammadiyah Yogyakarta, 2023)
Introduction Pain in post SC patients makes the patient disturbed and uncomfortable. This sensation makes the individual feel tormented, eventually interfering with activities, affecting sleep quality, and slowing down the wound healing process. One of the CAM methods used is hand and foot massage. Purpose To know how the hand and foot massage can influence in pain levels in postpartum mothers after post-cesarean. Methodology The method used is a case report taken during practice at PKU Muhammadiyah Bantul Hospital. The case report taken by the researcher was the patient Mrs A is 28 years old G0P1A0 with 39+1 weeks of gestation for indications of premature rupture membranes and breech presentation of the baby. The patient said this was the patient's first experience of doing an SC and the first experience of feeling post-SC pain. The patient was given massage therapy with hand and foot massage on post-SC postpartum mothers, the massage therapy on hand and foot for 2x24 hours. The Hand and foot massage therapy was given to the patient three times a day, a duration of 5 minutes for hands massage and 10-15 minutes for foot massage. Finding The level pain of a postpartum mother will decreased after hand and foot massage. The level of pain from postpartum mother will decrease from 6 to 3-4 after given foot and hand massage. This case report can be used as a CAM therapy to make pain in postpartum mothers with SC decreased.